Răspuns :
Răspuns:
Explicație pas cu pas:
b)
[tex] \frac{ \sqrt{48} + \sqrt{12} }{ \sqrt{3} } = \frac{ \sqrt{48} }{ \sqrt{3} } + \frac{ \sqrt{12} }{ \sqrt{3} } = \sqrt{ \frac{48}{3} } + \sqrt{ \frac{12}{3} } = \boxed{\sqrt{16} - \sqrt{4} } \\ [/tex]
c)
[tex] \frac{ \sqrt{18} - \sqrt{6} }{ \sqrt{2} } = \frac{ \sqrt{18} }{ \sqrt{2} } - \frac{ \sqrt{6} }{ \sqrt{2} } = \sqrt{ \frac{18}{2} } - \sqrt{ \frac{6}{2} } = \boxed{\sqrt{9} - \sqrt{3} } \\ [/tex]
d)
[tex] \frac{ \sqrt{99} + \sqrt{44} }{ \sqrt{11} } = \frac{ \sqrt{99} }{ \sqrt{11} } + \frac{ \sqrt{44} }{ \sqrt{11} } = \sqrt{ \frac{99}{11} } + \sqrt{ \frac{44}{11} } =\boxed{ \sqrt{9} - \sqrt{4} } \\ [/tex]